2006
DOI: 10.1063/1.2339040
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring light polarization in vertical cavity surface emitting lasers by isotropic optical feedback from an extremely short external cavity

Abstract: The authors experimentally show that isotropic optical feedback from an extremely short external cavity can induce switching between the two fundamental transverse modes with orthogonal linear polarization of otherwise (without optical feedback) polarization stable vertical cavity surface emitting laser. The switching currents and the hysteresis width can be widely tuned by varying the external cavity length. Moreover, by a proper choice of the optical feedback parameters, the emission can be stabilized in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For example VCSELs based on noncylindrical cavities, on spatial gain or loss anisotropy, on the use of external stress or optical feedback have been successfully realized. 5,[9][10][11] They show a polarization control toward a specific direction, with an orthogonal polarization suppression ratio ͑OPSR͒ being for the best value close to 30 dB. Nevertheless, most of these realizations increase the fabrication complexity and cost.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…For example VCSELs based on noncylindrical cavities, on spatial gain or loss anisotropy, on the use of external stress or optical feedback have been successfully realized. 5,[9][10][11] They show a polarization control toward a specific direction, with an orthogonal polarization suppression ratio ͑OPSR͒ being for the best value close to 30 dB. Nevertheless, most of these realizations increase the fabrication complexity and cost.…”
mentioning
confidence: 96%
“…[5][6][7][9][10][11] We believe that the fixed polarization and such an important and stable OPSR are mainly due to the QDH in-plane optical anisotropy. Ukhanov et al 20 have reported a QDH TE gain ratio close to 2 in linear SOA, depending of the QDH alignment ͑parallel or perpendicular͒ in reference to the SOA cavity axis.…”
mentioning
confidence: 98%